A sense of unease: elite high school students negotiating historical privilege. (2nd January 2022) - Halvorsen, Pål
ABSTRACT: The Scandinavian public school systems are free of charge and are central institutions upholding the egalitarian ideals that these societies are famous for. However, they do provide some students with privileged resources and enables trajectories that are out of reach for others. In this article, we address how students at two elite high schools in central Oslo acquire knowledge and relate to the 'eliteness' of their schools. Through individual interviews with 73 students we arrive at a closer understanding of elite schools and privileged students in the Norwegian school system. The two schools, Oslo Commerce School (OCS) and Schola Osloensis (SO), share elite characteristics, but have strikingly different school cultures. Their elite identification is examined through looking at their attitude towards learning, school work and elite status. The study unfolds how the 'ease' often associated with elite education is not necessarily developed, and is acquired in different ways. This glimpse into Norwegian elite schooling offers a challenge to the generalizability of studies from more market-oriented school systems.